2017
DOI: 10.1007/s12022-017-9481-8
|View full text |Cite
|
Sign up to set email alerts
|

Gangliocytic Paraganglioma: a Diagnostic Pitfall of Rare Neuroendocrine Tumor

Abstract: Dear Editor:We wish to comment on the gangliocytic paraganglioma research. Since hypoxia-inducible factor 2α gain-of-function mutations were detected in gangliocytic paraganglioma (GP) [1], as well as paraganglioma and somatostatinoma [2], this neuroendocrine tumor may be relative tumors of paraganglioma and/or somatostatinoma. In fact, there are similar morphological and immunohistochemical features between paraganglioma and GP, except for the existence of ganglion-like cell in GP [3]. In addition, GP often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…And it has also been reported that GP accounts for ~40% of duodenal NETs (15). GPs show better prognosis compared with G1 NETs (16), thus it is important to differentiate GPs from NETs. Morphologically, GP comprises three characteristic cell types: epithelioid cells, spindle-shaped cells and ganglion-like cells.…”
Section: Discussionmentioning
confidence: 99%
“…And it has also been reported that GP accounts for ~40% of duodenal NETs (15). GPs show better prognosis compared with G1 NETs (16), thus it is important to differentiate GPs from NETs. Morphologically, GP comprises three characteristic cell types: epithelioid cells, spindle-shaped cells and ganglion-like cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, pathologists should consider the primary lesion and the presence of ganglion-like cells. For instance, ganglion-like cells are absent from paraganglioma, which rarely arises from the duodenum ( 46 ). Although NET G1 is the most important differential diagnosis, GP is often misdiagnosed as NET G1 ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is important to distinguish between GP and NET G1. However, morphological and immunohistochemical similarities between GP and NET G1 may lead to misdiagnosis[8,9]. Thus, oncologists, clinicians, and pathologists should be aware of the concept of GP because our previous study suggests that GP accounts for a consistent proportion of NETs arising from the duodenum[10].…”
Section: Introductionmentioning
confidence: 99%